Analysis of the Relationship Between Organizational Culture, Training, and Employee Performance Via the Lens of Participatory Leadership, with Work Satisfaction Acting as a Moderator - Herman MS; Dhenny Asmarazisa; Catur Fatchu Ukhriyawati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Employee performance over the past three years has been all over the place, therefore something needs to be done about it. With employee job satisfaction serving as a moderating variable, this study seeks to further analyse the effects of participatory leadership, organisational culture, and training on employee performance. The researchers in this study drew their 100-person sample using the Slovin technique. The hypothesis test found that there was a positive and statistically significant relationship between employee performance and factors such as participative leadership, organisational culture, and job satisfaction. The impact of training on employee performance was unfavourable but not statistically significant. Employee Job Satisfaction was found to moderate the association between Organisational Culture and Employee Performance, according to the results of the moderation test.